2020
DOI: 10.1080/03004279.2020.1849346
|View full text |Cite
|
Sign up to set email alerts
|

Polish teachers of early education in the face of distance learning during the COVID-19 pandemic – the difficulties experienced and suggestions for the future

Abstract: Over 1.5 billion children from around the world were affected by school or university closures during the early phase of the COVID-19 pandemic in 2020 and distance learning was introduced for many pupils. The article presents the results of a survey conducted among Polish teachers of early education (N = 239), which aimed at answering an important question: To what extent and in what ways did Polish teachers cope with distance learning during the pandemic? The results of the survey revealed the many problems t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
67
0
13

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(82 citation statements)
references
References 10 publications
2
67
0
13
Order By: Relevance
“…In this study, a number of teachers complain about the number of objectives in the curriculum and suggest that certain objectives need to be taken out of the curriculum during the EDD process and that course durations need to be adjusted depending on the course content. Students were obliged to be a part of distance education for the first time and, suddenly, course lengths in online settings were less than those in face-to-face education, which negatively affected the quality of distance education (Kruszewska et al, 2020 ; Kufi et al, 2020 ). In this context, it may be concluded that the curricula used in face-to-face education were not suitable for the EDD.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, a number of teachers complain about the number of objectives in the curriculum and suggest that certain objectives need to be taken out of the curriculum during the EDD process and that course durations need to be adjusted depending on the course content. Students were obliged to be a part of distance education for the first time and, suddenly, course lengths in online settings were less than those in face-to-face education, which negatively affected the quality of distance education (Kruszewska et al, 2020 ; Kufi et al, 2020 ). In this context, it may be concluded that the curricula used in face-to-face education were not suitable for the EDD.…”
Section: Discussion Conclusion and Suggestionsmentioning
confidence: 99%
“…In addition, the fact that teachers and students had to switch to distance education suddenly became a popular topic for research during the pandemic (Hodges et al, 2020 ). Studies mainly focus on the success of distance education (Shire et al, 2020 ), the problems experienced (Adarkwah, 2020 ; Kruszewska et al, 2020 ), the factors affecting the use of the e-learning systems (Almaiah et al, 2020 ), measurement and evaluation processes (Butler-Henderson & Crawford, 2020 ), digital skills for distance education (Deshmukh, 2020 ), students' acceptance of online learning (Aguilera-Hermida, 2020 ), communication problems (Burke & Dempsey, 2020 ), and privacy issues in online settings (Gong, 2020 ). Although there are studies emphasizing the need to develop online education programs, in addition to the existing curricula due to the pandemic (Metchik et al, 2020 ; Wlodarczyk et al, 2020 ), none of the studies focus on the implementation of existing curricula in online learning environments.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of contact with students, especially in primary and secondary schools, deflected teachers' opinions on problems in motivating them [27]. What was also pointed out was the correlation between the effectiveness of online learning with factors such as design and preparation of the materials, the engagement of the teacher, and the possibility of the lecturer-student or student-student interactions [18].…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, there are studies aimed at determining teachers' views on the pandemic process. Many teachers state that their experience with emergency remote teaching provides important indicators that can help further improve online learning approaches with young children (Kruszewska, Nazaruk & Szewczyk, 2020). It is also mentioned in the studies that the rush in the first period of the pandemic has been overcome and the new normal conditions in education (Korkmaz & Toraman, 2020).…”
Section: Introductionmentioning
confidence: 99%